Salty, sour and umami taste threshold, body mass index and preferences of Filipino young adult - Enriquez, Lovely Cindy Yutuc
ABSTRACT The study assessed the relationship of salty, sour and umami taste thresholds with the body mass index (BMI) and food preferences of the Filipino young adult respondents. A total of 55 (13 males and 42 females) Filipino young adults, aged 20 to 35 years old, classified in terms of their BMI, were used as respondents. Food preference checklist was administered to the respondents using the 9-point hedonic scale. The salty, sour and umami taste thresholds were determined using the 3-Alternative Forced Choice (3-AFC)method. Age had a significant (p<0.05) effect on the preference for the foods identified with salty and umami tastes. On the other hand, no association (p>0.05) was found between food preferences and sex. Preferences for fruits and products and milk and dairy products were negatively associated (p<0.05) with BMI. Salty and umami taste thresholds were positively correlated (p<0.05) with age and both age and BMI, respectively. However, no clear associations (p>0.05) were found between salty, sour, and umami taste thresholds, and food preferences.